2022
DOI: 10.3390/separations10010021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Activity and Cytotoxicity Effects of Extracts of Piper nigrum L. and Piperine

Abstract: P. nigrum L. extracts and the piperine alkaloid have important antimicrobial, anti-inflammatory, and antioxidant properties. Therefore, in this study, we evaluated the antimicrobial activity and cytotoxicity of P. nigrum L. extracts and piperine, a compound isolated from the extracts of P. nigrum L. Extracts obtained via maceration, soxhlet, and purification steps, in addition to isolated piperine, were used in this study. Spectroscopic methods, such as nuclear magnetic resonance, scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 62 publications
3
9
0
2
Order By: Relevance
“…Derek software [ 19 , 20 ] classifies potentially toxic compounds into six categories: right, probable, plausible, implausible, improbable, or impossible ( Table 4 ). The compounds were classified in the plausible category.…”
Section: Resultsmentioning
confidence: 99%
“…Derek software [ 19 , 20 ] classifies potentially toxic compounds into six categories: right, probable, plausible, implausible, improbable, or impossible ( Table 4 ). The compounds were classified in the plausible category.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ZnO NPs have shown potential in inhibiting bio lm formation, a crucial factor in the pathogenesis of dental infections [22]. PIP, on the other hand, possesses antimicrobial properties and has been reported to enhance the bioavailability and e cacy of various drugs [23]. The synergistic action of ZnO NPs and PIP can enhance the antimicrobial activity against dental pathogens by targeting multiple pathways involved in microbial growth and bio lm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that piperine antimicrobial activity and cytotoxicity effects can be verified through molecular modeling. [ 33 , 34 ] Additionally, molecular modeling can also confirm the clinical therapeutic effects of different components such as geissoschizoline N4-methylchlorine and Eleutherine plicata by simulating molecular docking. [ 35 , 36 ] Consequently, in silico modeling offers the potential to develop new drug candidate ingredients with targeted effects.…”
Section: Discussionmentioning
confidence: 99%